2014
DOI: 10.4067/s0718-34292014000400008
|View full text |Cite
|
Sign up to set email alerts
|

Producción de pan de abejas (Apis mellifera L.) bajo condiciones de laboratorio

Abstract: RESUMENEl objetivo de este trabajo fue fabricar pan de abejas bajo condiciones de laboratorio a partir de sus ingredientes constitutivos por medio de procesos fermentativos evaluando sus características bromatológicas. Para ello se extrajo pan de abejas como inóculo desde panales de Apis mellifera para la fermentación del polen con miel. El ensayo estuvo constituido por seis tratamientos con tres repeticiones cada uno. Los tratamientos fueron: T 0 : polen sin inóculo, T 1 : pan de abejas natural, T 2 : polen +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In bee bread pH ranged from 3.8 to 4.3 (Herbert & Shimanuki, 1978) and 3.93 to 4.23 (Barene, Daberte, & Siksna, 2015) and bee bread fermented for fifteen days produced in the laboratory from 3.89 to 4.24 (Ríos et al, 2014). While in laboratory-produced fermented bee bread for twenty days pH ranged from 3.83 to 4.25 (Araneda et al, 2014). In pollen analyzes the pH ranged from 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In bee bread pH ranged from 3.8 to 4.3 (Herbert & Shimanuki, 1978) and 3.93 to 4.23 (Barene, Daberte, & Siksna, 2015) and bee bread fermented for fifteen days produced in the laboratory from 3.89 to 4.24 (Ríos et al, 2014). While in laboratory-produced fermented bee bread for twenty days pH ranged from 3.83 to 4.25 (Araneda et al, 2014). In pollen analyzes the pH ranged from 4.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzes prior to the experiment were performed to verify which variables could contribute positively to the fermentation of the protein supplement. It was observed that temperature, moisture, possible probiotics (Fuenmayor, Quicazán, & Figueroa, 2011;Ríos et al, 2012;Araneda et al, 2014;Ríos et al, 2014) and inulin (Vamanu et al, 2010) would be important variables. Possible probiotics had only efficient activity when used together.…”
Section: Variables Analyzedmentioning
confidence: 99%
See 1 more Smart Citation